(untitled) (Academicia Globe: Inderscience Research, 2023)
Before, during, and after the First World War, drama, poetry, and fiction were formed, and the period rich in war stories left its mark in all kinds of books. The literature of the "Lost Generation" is one of the terms that emerged in European and American literature in the decade after the end of the First World War. It is no exaggeration to say that the books of representatives of the so-called "lost generation" (E. Hemingway, R. Aldington, E. M. Remarque) are popular in different countries of the world and are popular among readers. In this article, the representation of the theme of war in the realistic literature of the USA of the 20th century.